Dougla poetics : orientations of Indianness and mixedness in Trinidad - Kay, Kavyta (Critical mixed race studies, 2024)
The category of the Dougla, that is the mixed Indian/Black body located in Trinidad, exists at a crossroads between multiculturalist discourses and essentialist ideas of Indian and African identities. Racialisation is often erased under the deployment of hybridity, creolisation and the 'callaloo nation' as meta narratives. Such mixing is seen as quintessentially Trinidadian, yet ontological understandings of race continue to operate as a distinctive marker of difference, particularly in the specifically Indian/Black mixed-race body of the Dougla. Dougla Poetics: Orientations of Indianness and Mixedness in Trinidad explores the meaning and negotiation of mixedness and the category of Dougla for a group of young Trinidadian women. Dr Kavyta Kay examines race and gender as lived and configured through discursive processes, through a raced gender performativity lens, deployed at the level of aesthetics, nation and culture. Drawing on conversations which took place across a range of religiously inflected and multicultural spaces, Kavyta focuses on these racialised, gendered identities as linked to socially constructed norms and practices, as well as what their talk reveals in terms of fluid and fixed notions of mixing. Confronting both popular and scholarly debates on the relationships between raced identities, this book acts as a challenging corrective to mixed-race studies which often prioritise Black/white binaries in the Global North while excluding multiracial experiences across the Global South.